2010
DOI: 10.1002/qj.663
|View full text |Cite
|
Sign up to set email alerts
|

A planetary‐scale land–sea breeze circulation in East Asia and the western North Pacific

Abstract: The diurnal wind variation over the East Asian continent is commonly considered to be a combination of a land-sea breeze near the coast and a mountain-valley breeze along the slopes of the Tibetan Plateau. The local land-sea breeze along the coastline typically spans <100 km into the ocean. However, a detailed examination of the global reanalysis data suggests that this local land-sea breeze circulation apparently couples with the global-scale diurnal atmospheric pressure tide to produce a planetary-scale land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 48 publications
(74 reference statements)
4
52
0
Order By: Relevance
“…The spatial resolution of GEOS5 is 0.667 • longitude × 0.5 • latitude (about 66.7 km in longitude × 50 km in latitude, a scale smaller than that of a typical local land-sea breeze ∼100 km) which provides a good depiction of the regional diurnal wind variation (Huang et al, 2010). The precipitation analysis uses the TRMM (Tropical Rainfall Measuring Mission; Simpson et al, 1996) 3G68 2B31 dataset because it uses both passive and active microwave data to produce the best rain estimate for TRMM (Haddad et al, 1997a(Haddad et al, , 1997b, which has been shown to resemble rain gauge observations, with a good representation of the diurnal rainfall variability (Hong et al, 2005;Zhou et al, 2008;Chen et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The spatial resolution of GEOS5 is 0.667 • longitude × 0.5 • latitude (about 66.7 km in longitude × 50 km in latitude, a scale smaller than that of a typical local land-sea breeze ∼100 km) which provides a good depiction of the regional diurnal wind variation (Huang et al, 2010). The precipitation analysis uses the TRMM (Tropical Rainfall Measuring Mission; Simpson et al, 1996) 3G68 2B31 dataset because it uses both passive and active microwave data to produce the best rain estimate for TRMM (Haddad et al, 1997a(Haddad et al, , 1997b, which has been shown to resemble rain gauge observations, with a good representation of the diurnal rainfall variability (Hong et al, 2005;Zhou et al, 2008;Chen et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…7a). The role of −∇·Q in contributing to the change of diurnal rainfall variation over southeast China was examined by Huang et al (2010) through the diagnosis of water vapor budget equation.…”
Section: The Simulation Of Diurnal Variation At Present Climatementioning
confidence: 99%
“…1) that features non-propagating (afternoon) diurnal rainfall (e.g., Huang et al 2010). The mechanisms responsible to such a regional difference in diurnal rainfall have been studied extensively (e.g., Wallace 1975;Oki and Musiake 1994;Yang and Slingo 2001;Nesbitt and Zipser 2003;Sorooshian et al 2002;Yu et al 2007a, b;Huang et al 2010;Huang and Wang 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations